Pengaruh Pengumuman Right Issue Terhadap Abnormal Return Dan Volume Perdagangan Saham (Studi Kasus Pada Perusahaan Asuransi yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015) - Moch Kukuh Widyatmoko; Ronny Malavia Mardani; Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
Abstract “Right issue is an event that’s related to information’s publication as an announcement and can be used to observe the market reaction. Theoretically, the market reaction is measured by abnormal return and trading volume activity. This research used paired sample t-test to examine the effect of right issue’s announcement to the abnormal return and trading volume activity, using samples as much as 41 firms from 2009 to 2011. The observation period was 5 days before and 5 days after the announcement’s period. The result showed that the right issue’s announcement did not affect significantly to the abnormal return of firms, while affected significantly to the trading volume activity”.                Keyword: Abnormal Return, Right Issue, Trading Volume Activity